2017
DOI: 10.1063/1.4994137
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic damping in poly-crystalline Co25Fe75: Ferromagnetic resonance vs. spin wave propagation experiments

Abstract: We report on the investigation of the magnetic damping of a 10 nm thin, poly-crystalline Co 25 Fe 75 film grown by molecular beam epitaxy. Ferromagnetic resonance (FMR) measurements reveal a low intrinsic magnetic damping a FMR int ¼ ð1:560:1Þ Â 10 À3 . In contrast, in patterned micrometer wide stripes, spin wave (SW) propagation experiments performed by time resolved scanning magneto-optical Kerr microscopy yield attenuation lengths on the order of 5-8 lm. From this quantity, we deduce an effective magnetic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…One means to exclude the spin pumping contributions is epitaxial growth on insulating or semiconducting substrates. Indeed, two recent studies reported the growth of Co25Fe75 on MgO and MAO resulting in values of the damping parameters around 0.001 [11,12]. Removing the constraint of epitaxial growth on single crystalline substrates while maintaining low magnetic damping and high film uniformity may enable integration of this material in a wide range of spintronic and magnonic devices [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…One means to exclude the spin pumping contributions is epitaxial growth on insulating or semiconducting substrates. Indeed, two recent studies reported the growth of Co25Fe75 on MgO and MAO resulting in values of the damping parameters around 0.001 [11,12]. Removing the constraint of epitaxial growth on single crystalline substrates while maintaining low magnetic damping and high film uniformity may enable integration of this material in a wide range of spintronic and magnonic devices [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The data were experimentally obtained by Brillouin light scattering in the magnetostatic surface wave configuration in a Co25Fe75 magnonic conduit with a width of 5 µm and a thickness of 26 nm for an external magnetic field magnitude of 43 mT. The combination of high group velocity and record low intrinsic damping 𝛼 < 0.001 [65] results in experimentally observed spin-wave propagation lengths [70] Achievement of these high spin-wave propagation lengths requires suppression of two-magnon scattering and inhomogeneous relaxation effects [71].…”
Section: Metallic Ferromagnets With Ultralow Damping For Spinwave Wav...mentioning
confidence: 99%
“…Although this technique is versatile and powerful due to its phase-resolving capability and frequency accuracy, it is not able to capture the magnetization dynamics locally or in micro-structured devices. In patterned devices, magnetization dynamics are locally probed by optical techniques, such as the microfocused time-resolved magneto-optic Corresponding author: L. Liensberger (Lukas.Liensberger@wmi.badw.de) Kerr effect (µTR-MOKE) [12], [13], [14] or microfocused Brillouin Light Scattering (µBLS) [15], [16].…”
Section: Introductionmentioning
confidence: 99%